Civil-Patriotic education of students in the Republic of Kazakhstan - Gulbakhyt Zhumabekova, Maira Jilkishiyeva, (Opción, 2019)
In this research, we developed a concept of civil-patriotic education of student’s youth in conditions of modern multinational state based on the concept of a comprehensive program. In experimental work involved 460 students of 1-4 courses of study, of which 198 girls and 262 boys. Comparing the control and experimental groups showed the effectiveness of the developed program in raising the level of civil-patriotic education of youth, and the pedagogical observation of the behavior and the organization of educational and practical activities of students from the experimental group is elaborated on these results.